“You Rest, You Rust:” Intergenerational constructions of rest among Black women in Johannesburg, South Africa - Ndabane, Tshegofatso (Department of Psychology, 2025)
Over the last decade, there has been a rise in reports within mainstream media about Black women reclaiming their agency through rest. However, despite this recognized importance of rest as it relates to Black women, comparatively sparse research literature has examined this relationship. More specifically, the literature has failed to address Black women's constructions of rest in the context of the strong Black woman schema as a dominant feature of their gendered racial socialization experiences. The purpose of this study was to explore how a group of Black mothers and daughters construct their ideas and experiences of rest while navigating life within the South African context, as well as how these are negotiated from one generation to another. Drawing on a qualitative research design, four mother-daughter dyads participated in a series of eight individual interviews and four joint interviews. Black Feminist-Womanist Thought was the theoretical framework applied, and the thematic analysis by constant comparison analysis approach yielded four overarching themes: Participants' definitions of rest, how rest cannot be separated from the material and psychosocial realities of a post-apartheid South Africa, adultification of Black girls as a hidden feature of the strong Black woman schema which impacts articulations of rest, and intergenerational conversations as a site of affirmation, negotiation and education. The findings discussed within the identified themes ultimately advocate that we consider how the adultification of Black girls manifests itself into the strong Black women schema. Additionally, it serve as a foundation from which further discourse around rest and Black women in South Africa can be explored and produced.